Recent Advances in Ammonia Combustion Technology in Thermal Power Generation System for Carbon Emission Reduction - Hookyung Lee; Min-Jung Lee (Energies, 2021)
With the formation of an international carbon-neutral framework, interest in reducing greenhouse gas emissions is increasing. Ammonia is a carbon-free fuel that can be directly combusted with the role of an effective hydrogen energy carrier, and its application range is expanding. In particular, as research results applied to power generation systems such as gas turbines and coal-fired power plants have been reported, the technology to use them is gradually being advanced. In the present study, starting with a fundamental combustion research case conducted to use ammonia as a fuel, the application research case for gas turbines and coal-fired power plants was analyzed. Finally, we report the results of the ammonia-air burning flame and pulverized coal-ammonia-air co-fired research conducted at the authors’ research institute.